Alcohol consumption and related disorders in Iran: Results from the National Surveillance of Non-Communicable Diseases' Survey (STEPs) 2016 - Negar Rezaei; Naser Ahmadi; Mehran Shams Beyranvand; Milad Hasan; Kimiya Gohari; Moein Yoosefi; Shirin Djalalinia; Sahar Saeedi Moghaddam; Mitra Modirian; Forough Pazhuheian; Alireza Mahdavihezaveh; Ghobad Moradi; et al. (Public Library of Science (PLoS), 2022)
Background Alcohol consumption is a public health concern which is illegal in Iran. Moreover, due to cultural and religious beliefs, the available population-based research findings on alcohol consumption are inadequate. We aimed to provide an estimate on alcohol consumption using a large-scale population-based survey in Iran. Materials and methods The National Surveillance of Non-Communicable Risk Factors in Iran was a population-based survey conducted in 2016. The epidemiologic distribution of alcohol consumption and its related disorders were assessed using weighted survey methods and multiple logistic regression models. Age standardized rates were calculated using Iran's national population census in 2016. Results At the national level, the prevalence rates of lifetime and current alcohol consumption were 8.00% (95% CI: 7.67-8.32) and 4.04% (95% CI: 3.81-4.27), respectively. The highest prevalence was reported among 25 to 34 year-olds. Individuals of higher socioeconomic status consumed significantly greater levels of alcohol. At provincial level, the highest and lowest percentages of the current alcohol drinking rates in Iran's provinces were, 23.92% (95% CI: 17.56-30.28) and 0.4% (95% CI: 0-1.18) in males, 1.58% (95% CI: 0.22-2.94) and 0% in females, respectively. In urban regions, the highest alcohol consumption rate was more than 22 times greater than the lowest alcohol consumption rate. Current alcohol drinkers were 2 times more prone to injury as compared to nondrinkers (ORadj: 2.0, 95%CI: 1.7, 2.3). Conclusion In Iran, the prevalence of alcohol consumption is low, although there is a considerable variation of alcohol consumption at provincial level as well as in different gender groups. Therefore, preventive WHO-recommended measures should be adopted more seriously by vulnerable groups.